Delegated disabling affects in partnership - Tröndle, Judith (Frontiers in Sociology, 2025)
The social and cultural understanding of disability has indicated that it is primarily a consequence of attributional processes, idealized and generalized conceptions of ability, and structural discrimination. Assuming the validity of these conceptualizations, the focus shifts to relational dynamics that determine how and if disability is ‘felt.’ This study explores this relationality in the context of couples parenting a child with disabilities. Intersections of gender and disability associated with self-positioning as ‘special parents’ include specific affective couple arrangements. This study reports on a qualitative study using in-depth interviews with couples who were interviewed first together and then individually. The results indicate a subjectivation of couples as ‘special parents,’ which is difficult to reject and includes affective aspects as well as gendered inequalities in care. Disabling affects are delegated to and felt by the female partner, leading to affective inequalities in the partnership. The couple positions the mother as the one who ‘suffers,’ which is part of a well-known affective repertoire that is implied by ableism to feel. The theoretical implications of these empirical results will be discussed as twofold: first, as an entry point to understanding disability via affection—how to be affected by disability along intersected cultural attributions; and second, as a suggestion to bridge cognitive and behavioral approaches to emotion by elaborating on how disabling affects become felt and enacted in subjectivation and relation.